IOC consensus statement: dietary supplements and the high-performance athlete - Maughan, R. J.; Burke, L. M.; Dvorak, J.; Larson-Meyer, D. E.; Peeling, P.; Phillips, S. M.; Rawson, E. S.; Walsh, N. P.; Garthe, I.; Geyer, H.; Meeusen, R.; van Loon, L. J. C.; et al. (British Journal of Sports Medicine, 2018)
Nutrition usually makes a small but potentially valuable contribution to successful performance in elite athletes, and dietary supplements can make a minor contribution to this nutrition programme. Nonetheless, supplement use is widespread at all levels of sport. Products described as supplements target different issues, including (1) the management of micronutrient deficiencies, (2) supply of convenient forms of energy and macronutrients, and (3) provision of direct benefits to performance or (4) indirect benefits such as supporting intense training regimens. The appropriate use of some supplements can benefit the athlete, but others may harm the athlete`s health, performance, and/or livelihood and reputation (if an antidoping rule violation results). A complete nutritional assessment should be undertaken before decisions regarding supplement use are made. Supplements claiming to directly or indirectly enhance performance are typically the largest group of products marketed to athletes, but only a few (including caffeine, creatine, specific buffering agents and nitrate) have good evidence of benefits. However, responses are affected by the scenario of use and may vary widely between individuals because of factors that include genetics, the microbiome and habitual diet. Supplements intended to enhance performance should be thoroughly trialled in training or simulated competition before being used in competition. Inadvertent ingestion of substances prohibited under the antidoping codes that govern elite sport is a known risk of taking some supplements. Protection of the athlete`s health and awareness of the potential for harm must be paramount; expert professional opinion and assistance is strongly advised before an athlete embarks on supplement use.